2018
DOI: 10.1021/acs.molpharmaceut.7b00722
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Expression Kinetics and Immunostimulatory Activity of Replicating mRNA, Nonreplicating mRNA, and pDNA after Intradermal Electroporation in Pigs

Abstract: Synthetic mRNA is becoming increasingly popular as an alternative to pDNA-based gene therapy. Currently, multiple synthetic mRNA platforms have been developed. In this study we investigated the expression kinetics and the changes in mRNA encoding cytokine and chemokine levels following intradermal electroporation in pigs of pDNA, self-replicating mRNA, and modified and unmodified mRNA. The self-replicating mRNA tended to induce the highest protein expression, followed by pDNA, modified mRNA, and unmodified mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Similar superior kinetics and potency have been previously described for CNE-formulated self-amplifying mRNA. 108 Leyman et al 109 recently compared luciferase expression of self-amplifying mRNA, nucleoside-modified conventional mRNA, and unmodified conventional mRNA after i.d. electroporation in pigs.…”
Section: Self-amplifying Mrna Vaccinesmentioning
confidence: 99%
“…Similar superior kinetics and potency have been previously described for CNE-formulated self-amplifying mRNA. 108 Leyman et al 109 recently compared luciferase expression of self-amplifying mRNA, nucleoside-modified conventional mRNA, and unmodified conventional mRNA after i.d. electroporation in pigs.…”
Section: Self-amplifying Mrna Vaccinesmentioning
confidence: 99%
“…Synthetic self-amplifying mRNAs are known for their high in vivo translational efficiency [21,22]. However, in vivo administration of sa-mRNAs may induce a strong type I IFN response [5,11,23]. While this can be considered advantageous when the sa-mRNA is used for vaccination purposes [11,24], several studies have demonstrated that triggering type I IFN production can negatively impact the intended adaptive immune response of intramuscularly and intradermally administered mRNA vaccines [9,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, synthetic mRNAs allow cell-free production and exert a transient and more predictable expression [1,2]. In recent years, synthetic self-amplifying mRNAs (sa-mRNAs) have also been gaining interest because of their higher and longer-lasting expression compared to non-amplifying mRNAs [4,5]. Self-amplifying RNAs encode an RNAdependent RNA polymerase (replicase) that gives them the capacity to trigger a temporal amplification of their backbone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if the innate immune response has not faded away at the moment of the next mRNA injection a chronical inflammatory condition will be established. The duration of the innate immune response after in vivo delivery of mRNA is not well studied and most information comes from studies that used RT-PCR or ELISA to quantify key innate immune proteins [22][23][24]. Although RT-PCR is a very sensitive technique, the correlation between mRNA levels and protein expression are not always linear [25].…”
Section: Introductionmentioning
confidence: 99%